P271 Rates of resectable bronchiectasis and introduction of a referral framework for surgical management of bronchiectasis. (15th November 2016) - Barmayehvar, B; Nguyen, TC; Sullivan, A; Kalkat, M
Abstract : Introduction: Bronchiectasis can cause significant complications and severely impact on patients' quality of life. The majority of patients can be managed by medical therapy. Although lung resection is a less popular option, it is still reserved for a small number of patients with refractory symptoms, antibiotic-resistant bacteria or complications. The BTS guideline recommends: "Lung resection surgery may be considered in patients with localised disease in whom symptoms are not controlled by medical treatment". However, the lack of a clear referral framework means respiratory physicians may have missed valuable opportunities to discuss the option of surgery. Thus, we aim to raise awareness about this option among physicians. At a tertiary bronchiectasis clinic, we investigated the proportions of patients with resectable disease and whether appropriate surgical referrals were made. Development of a referral framework was later proposed. Methods: This is a retrospective study assessing all patients under the care of the bronchiectasis clinic at Queen Elizabeth Hospital Birmingham. The collected data included clinic letters, CT scan and spirometry reports. Based on surgical criteria, we developed a pathway to identify potential candidates for surgery. Their clinic letters were reviewed to determine whether the surgical option had been considered. A literature review was undertaken to identify key factors needed to develop a referral framework. Results: Among 381 patients identified, 19 patients were excluded having insufficient data and 30 having undergone previous lung resection. In the remaining 322 patients (Figure 1 ), 89 patients had localised disease, were fit, with adequate respiratory reserve. In this group, we further identified 8 patients (2% of study population) who were potential candidates for surgery. None of these patients had been considered for surgery. Following a discussion at the Midland Bronchiectasis Network meeting with input from experienced thoracic surgeons, a referral framework was generated to assist physicians in identifying potential candidates. Conclusions: We identified 8 patients who could benefit from surgery. Although they constitute a small proportion of the study population (2%), the result suggests respiratory physicians may be under-referring patients for surgery. A referral framework is introduced to assist physicians in referring appropriate patients to a surgical team.